SHIP is required for a functional hematopoietic stem cell niche - Hazen, Amy L. (American Society of Hematology, 2009)
SH2-domain-containing inositol 5′-phosphatase-1 (SHIP) deficiency significantly increases the number of hematopoietic stem cells (HSCs) present in the bone marrow (BM). However, the reconstitution capacity of these HSCs is severely impaired, suggesting that SHIP expression might be an intrinsic requirement for HSC function. To further examine this question, we developed a model in which SHIP expression is ablated in HSCs while they are resident in a SHIP-competent milieu. In this setting, we find that long-term repopulation by SHIP-deficient HSCs is not compromised. Moreover, SHIP-deficient HSCs from this model repopulate at levels comparable with wild-type HSCs upon serial transfer. However, when HSCs from mice with systemic ablation of SHIP are transplanted, they are functionally compromised for repopulation. These findings demonstrate that SHIP is not an intrinsic requirement for HSC function, but rather that SHIP is required for the BM milieu to support functionally competent HSCs. Consistent with these findings, cells that comprise the BM niche express SHIP and SHIP deficiency profoundly alters their function.